THE APPLICATION OF PROBLEM-BASED LEARNING MODEL TO THE LEARNING OUTCOMES ON EXPONENT FUNCTION OF FIRST GRADE STUDENTS IN KRUENG BARONA JAYASENIOR HIGH SCHOO - Rahmat Fitra; Nurul Ariescha; Yuli Amalia (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The lack of teacher creativity in implementing learning results in low student learning outcomes. One way to improve student learning outcomes is to use a learning model that focuses on student activeness. This study aims to determine the effect of applying the Problem Based Learning learning model on student learning outcomes in exponent functions in first grade students at Krueng barona Jaya senior high school. The type of research used is quasi-experimental with Pretest Posttest Control Group Design. Sampling based on purposive sampling technique, obtained X1 class students (N = 24) as an experimental class that applies learning with Problem Based Learning model and X2 class students (N = 28) as a control class that applies conventional learning. Data collection techniques using observation, tests and documentation. Based on the results of the t-test analysis of two independent samples through the average value of the posttest of student learning outcomes, obtained t-count > t-table (4.49> 2.00). So it can be concluded that there is an effect of learning using the Problem Based Learning model on student learning outcomes on exponent function.